Evaluation of Chickpea (Cicer arietinum L.) Genotypes based on Morphological Traits in Vindhya Region of Uttar Pradesh, India - Baira Naresh; Bineeta Michael. Bara; Gaibriyal M. Lal; Vaidurya Pratap Sahi (Archives of Current Research International, 2024)
The study was conducted in the Field Experimentation Centre, Department of Genetics and Plant Breeding, Naini Agricultural Institute, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj (Uttar Pradesh) during Rabi, 2023-2024. The soil of experimental plot was sandy loam in texture, nearly neutral in soil reaction (pH 7.1), low in organic carbon (0.36 %), available N (171.48 kg/ha), available P (15.2 kg/ha) and available K (232.5 kg/ha). The experiment was laid out in Randomized Block Design with fifteen genotypes which were replicated thrice. The results revealed that plant height (55.69 cm), No. of primary branches (3.19), number of secondary branches (10.34), no.of pods per plant (55.39), no. of seeds per plant (9.70), seed yield per plant (19.32 gm), seed yield per ha (3864.45 kg/ha), biological yield per plant (31.69 gm), harvest index (37.88%), seed index (19.38 gm), test weight (193.8gm), seed length (9.47 mm), seed width (8.23) were recorded highest in Phule Vikram genotype followed by PG-05 genotype and days to 50% flowering (56.79 DAS), days to 50% pod setting (81.09 DAS), days to maturity (117.43 DAS) were recorded the lowest in JG-16 genotype.